Income and Employment in the Southeast - McGee, L. Randolph (Book collections on Project MUSE., 1967)
Although there has been a growing interest in regional economic development, the important aspect of regional business fluctuations has not received corresponding attention. This study focuses upon the relative cyclical behavior of income and employment in the Southeastern United States following the Second World War and seeks to determine in particular what effect the industrial composition of the region has had upon income and employment. Using the procedures of the National Bureau of Economic Research, Mr. McGee identifies four complete cycles of general business activity during the postwar.